Analisis Etika dan Profesionalisme Akuntan serta Dampaknya Terhadap Lingkungan Sosial-Ekonomi: Sebuah Literatur Review - Tanelab, Gracia Ariella Jenice (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2022)
Ethics is a complex theory along with the growing community associations. Many new professions are created as the consequences of the efforts to fulfill society needs from time to time, and also influenced by the changes of social-economy environment. Because the needs to divide the work loads to the expert team in every different fields, professions become more consolidated and play crucial roles in building society welfares. The well-being of every profession are depend on the service quality provided, as well as society trust. Admiration and trust are the main keys for every profession to serve society. The accountant community in some countries have designed ethical profession to protect public and require accountant to oblige to the policies. This regulation aims to solve ethical problems in the near future.